Local Knowledge of Traditional Physician of Medicinal Plants - Salma Indah Kurniati; Yulianty Yulianty; Tundjung Tripeni Handayani; Martha L. Lande (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Traditional medicine in modern era has not been completely abandoned. Now, Traditional medicine is being used again as a substitute for the use of chemical drugs. West Baturaja, Ogan Komering Ulu, located in South Sumatra is an area in Indonesia that still uses traditional medicine. This research is conducted to study the knowledge of Traditional Physician in using medicinal plants for treatment in West Baturaja, Ogan Komering Ulu, South Sumatra. This research was conducted in 5 villages in West Baturaja. We interviewed 8 Traditional Physician from 5 villages, i.e. Talang Jawa Village (4 people), Air Gading (1 people), Saung Naga (1 people), Batu Putih (1 people), and Pusar village (1 people). The Result obtained that there are 140 types of medicinal plants from 60 families. The most widely used is the Zingiberaceae. The most widely used plant habitus is a bush. The most widely used part is the leaves. The way of processing is boiled then taken by the patient. The most commonly treated disease is diabetes.